Memakna Disiplin dalam Kehidupan SMK Negeri di Kabupaten Barito Selatan, Kalimantan Tengah - Siburian, Leonardo; Amiani A, Mia; Munthe, Yesyurun (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The researcher's research is motivated by the extent to which subjects or students in the context of understanding the term discipline in the scope of inside and outside the classroom. The extent of this understanding cannot be separated from the culture that students have received both in the family room and in the classroom. In addition, the assumption of many people that discipline is a negative impulse – that the institution or the term discipline exists to be violated – is not entirely true. However, in this paper, the author is not looking for the extent of the right and wrong percentage of the logical consequences of discipline. Instead, the author looks at the extent to which the narratives that are often not heard by the public appear in the writing of the research subject. This qualitative research uses the interview method by recording every conversation between the two parties, namely the interviewer and the research subject who comes from various SMKNs in Buntok, Central Kalimantan. Furthermore, the author transcribed the interviews from the audio recordings. The results of this study show that discipline should be in the space of dialog (discipline as a work in time) that is mutually beneficial between teachers and students. Thus, the negotiation space is important here. Then, the author found that learner independence is an implementative action of the current learning curriculum. Furthermore, the extent of discipline is the extent to which the limits of discipline are contained and applied in the school room.